Prevalence and Antibiograms of Uropathogens from the Suspected Cases of Urinary Tract Infections in Bharatpur Hospital, Nepal - Adhikari, Sanjib; Khadka, Sujan; Sapkota, Sanjeep; Rana, Jid Chani; Khanal, Santosh; Neupane, Asmita; Sharma, Babita (Journal of College of Medical Sciences-Nepal, 2019)
Background: This study was conducted to determine the prevalence and antibiotic susceptibility pattern of the uropathogens among the patients attending Bharatpur Hospital. Methods: A laboratory-based cross-sectional study was carried out among the patients attending Bharatpur Hospital from December 2017 to February 2018. Aseptically collected clean catch mid-stream urine samples from 200 clinically suspected patients were cultured and processed for the identification of the uropathogens in the laboratory using standard microbiological procedures. Antibiotic susceptibility test was performed for all the isolates against commonly used antibiotics using the Kirby-Bauer disc diffusion method according to Clinical and Laboratory Standards Institute guidelines 2017. Results: Out of 200 samples collected, 59(29.5%) of the samples showed the presence of pathogens causing urinary tract infection (UTI). Among them, 43(72.9%) were Gram-negative and 16(27.1%) were Gram-positive bacteria. UTI was found to be the most prevalent in females compared to the males and in the age group of 21-30 years. E. coli (72.0%) and Staphylococcus epidermidis (50.0%) were the most predominant Gram-negative and Gram-positive isolates respectively. The isolates were resistant to cefpodoxime (54.2%) and least resistant to gentamicin (10.2%). Twenty (33.9%) isolates were found to be multi-drug resistant (MDR). Conclusions: Higher frequency of antibiotic resistance among UTI patients alerts for continuous surveillance to assure effective control of this infection. Awareness of good hygienic practice especially in females and prudent use of antibiotics in case of infection can be sug-gested.